PENGGUNAAN TEKNOLOGI DENGAN SARANA VIDEO KONFERENSI DALAM PEMBUATAN AKTA - SITI MARYAM HANUM (PREMISE LAW JURNAL, 2019)
Law No 11/2008 on Electronic Information and Transaction (UUITE) gives anopportunity for the realization the concept of making Deeds by using technology withconference video. The research problems were how about legal certainty of a Notary’sauthority in making a deed through conference video, how about the validity of the personsappearing in the process of making a notarial deed through conference video, and howabout legal remedy in the implementation of making a deed deed through conference video.The research used juridical normative using secondary data and supported by interviews.Making adeed by using technlogy with conferencevideo is difficult to be implemented sincesome of these regulations are contrary to UUJN (Notarial Act) and the clauses in the UUKNrequire the persons appearing and the signing of the deeds. The exception is the Minutes ofRUPS which uses conference video stipulated in Article 77, paragraph 1 of UUPT and itsimplementation process is supported by UUITE. Meanwhile, there is no clear regulation onthe making of authentic deeds by technology. However, the validity of the persons appearingin the making deeds through conference video is possible viewed from Article 5 of UUITEwhich recognizes the validity of electronic information and electronic documents throughconference video. The legal force of the persons appearing in making deeds throughconference video, in law of civil procedure, is legal evidence since it has met material andformal requirements.Keywords: Notary, Technology, Conference Video